New insights on the trophic ecology of blue (Prionace glauca) and shortfin mako sharks (Isurus oxyrinchus) from the oceanic eastern South Pacific. Issue 2 (7th February 2018) - Klarian, Sebastian A.; Canales-Cerro, Carlos; Barría, Patricio; Zárate, Patricia; Concha, Francisco; Hernández, Sebastián; Heidemeyer, Maike; Sallaberry-Pincheira, Pauline; Meléndez, Roberto
ABSTRACT: The blue shark ( Prionace glauca ) and the shortfin mako shark ( Isurus oxyrinchus ) are two large and highly migratory sharks distributed in most oceans. Although they are often caught in the south Pacific Ocean long-line fisheries, their trophic ecology is poorly understood. Stable isotopes with Bayesian mixing and dependence concentration models were performed to determine the diet and trophic differences between the two species in the South-eastern Pacific Ocean. According to the mixing models, fishes are the most important prey of these sharks. Dolphin calves and remains were found in the stomachs of both species, which represents a novel finding in trophic ecology of South Pacific sharks. Intra-specific differences were found in P. glauca, but not in specimens of I. oxyrinchus . The two sharks showed a high degree of diet overlap (73%), primarily over mackerel and dolphin carcasses. Our results indicate that blue and shortfin mako sharks have a generalist feeding strategy in the eastern Pacific Ocean, with a strong preference for teleost fishes and also for dolphin carcasses. Therefore, trophic studies are useful to understand energy flow through the food web, and the trophic position of key species.